2022
DOI: 10.3390/stresses3010004
|View full text |Cite
|
Sign up to set email alerts
|

Prominent Effects of Zinc Oxide Nanoparticles on Roots of Rice (Oryza sativa L.) Grown under Salinity Stress

Abstract: The morphological plasticity of plant roots is a key factor in their ability to tolerate a wide range of edaphic stresses. There are many unanswered questions relating to nanotechnology and its potential uses for sustainable agriculture. The main purpose of this study was to examine the effects of salinity-induced morphogenic responses and zinc oxide nanoparticles (ZnO-NPs) on root characteristics, growth, MDA content, antioxidant enzymatic activity, and root ion accumulation in rice (Oryza sativa L.). The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Plants of maize and cotton also produced comparable results [54,56]. In earlier studies, a link was found between an increase in harmful ions (Na + and Cl -) and a decrease in the absorption of critical components required for growth, as seen by the high Na + /K + ratio for salt-treated basil plants [62,88]. Salinity also causes a significant reduction in the fruit and seed yield of commercially important crops [14,53,54,89,90].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Plants of maize and cotton also produced comparable results [54,56]. In earlier studies, a link was found between an increase in harmful ions (Na + and Cl -) and a decrease in the absorption of critical components required for growth, as seen by the high Na + /K + ratio for salt-treated basil plants [62,88]. Salinity also causes a significant reduction in the fruit and seed yield of commercially important crops [14,53,54,89,90].…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, the foliar spray of Zn as ZnO NPs helps provide the nutritional requirements of Zn in the plants [33]. In the agriculture sector, Zn doses proved potent to reduce salinityinduced toxicity on basil plants [62], but the foliar spray of NPs such as ZnO and other nutrients released in a controlled manner made the macromolecule delivery more selective and effective [21,88,105]. Foliar spray of ZnO NPs also enhances the expression level of genes encoding Rubisco-and chlorophyll-binding proteins, increases proline production and accumulation, and increases the antioxidant activity of plants by regulating the gene activation responsible for proline production and antioxidant activities [21,84,86,105].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the enhanced Cu 2+ and Mn 2+ uptake by ZnO-NPs is multifaceted. ZnO-NPs enhance the root surface area, providing more sites for Cu 2+ and Mn 2+ adsorption (Abuhatab et al, 2020;Singh et al, 2022b). These nanoparticles also stimulate root hair development, increasing nutrient absorption capacity.…”
Section: Singh Et Al (2021) Observed That the Application Ofmentioning
confidence: 99%
“…However, the outer layers of the root hair and root tip epidermis of both primary and secondary plant roots are still developing. Here, the exposure of NPs causes them to immediately enter and come into contact with the root epidermis (Rajput et al 2018 ; Singh et al 2022 ). Root epidermal cells have a permeable cell membrane that allows certain nutrients as well as water to pass through.…”
Section: Nanotechnological Approaches For Remediation Of Hmmsmentioning
confidence: 99%